Theoretical Study on Singlet Fission Dynamics and Triplet Migration Process in Symmetric Heterotrimer Models - Hajime Miyamoto; Kenji Okada; Kohei Tada; Ryohei Kishi; Yasutaka Kitagawa (Molecules, 2024)
Singlet fission (SF) is a photophysical process where one singlet exciton splits into two triplet excitons. To construct design guidelines for engineering directional triplet exciton migration, we investigated the SF dynamics in symmetric linear heterotrimer systems consisting of different unsubstituted or 6,13-disubstituted pentacene derivatives denoted as X/Y (X, Y: terminal and center monomer species). Time-dependent density functional theory (TDDFT) calculations clarified that the induction effects of the substituents, represented as Hammett’s para-substitution coefficients <semantics>σp</semantics>, correlated with both the excitation energies of S1 and T1 states, in addition to the energies of the highest occupied and lowest unoccupied molecular orbitals (HOMO and LUMO). Electronic coupling calculations and quantum dynamics simulations revealed that the selectivity of spatially separated TT states for heterotrimers increased over 70%, superior to that in the homotrimer: an optimal region of the difference in <semantics>σp</semantics> between the substituents of X and Y for the increase in SF rate was found. The origin of the rise in SF rate is explained by considering the quantum interference effect: reduction in structural symmetry opens new interaction paths, allowing the S1-TT mixing, which contributes to accelerating the hetero-fission between the terminal and center molecules.